2012
DOI: 10.1186/1745-6215-13-193
|View full text |Cite
|
Sign up to set email alerts
|

Surgical trial in traumatic intracerebral hemorrhage (STITCH(Trauma)): study protocol for a randomized controlled trial

Abstract: BackgroundIntracranial hemorrhage occurs in over 60% of severe head injuries in one of three types: extradural (EDH); subdural (SDH); and intraparenchymal (TICH). Prompt surgical removal of significant SDH and EDH is established and widely accepted. However, TICH is more common and is found in more than 40% of severe head injuries. It is associated with a worse outcome but the role for surgical removal remains undefined. Surgical practice in the treatment of TICHs differs widely around the world. The aim of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…This becomes even more important when we realize that surgery is very effective in patients of SDH and that the results are far better with an early surgical intervention rather than if it is delayed. 11 Finally we recommend that patients with ocular motor nerve palsy should always be carefully examined in close collaboration with other specialists, especially where sophisticated, complementary investigations are not available.…”
Section: Resultsmentioning
confidence: 99%
“…This becomes even more important when we realize that surgery is very effective in patients of SDH and that the results are far better with an early surgical intervention rather than if it is delayed. 11 Finally we recommend that patients with ocular motor nerve palsy should always be carefully examined in close collaboration with other specialists, especially where sophisticated, complementary investigations are not available.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the only trial investigating the role of early surgery versus initial conservative treatment to anticipate and prevent secondary damage in traumatic ICH was halted early. 43,44 Although the evidence is limited due to the low sample size resulting from premature termination, it appears that the STITCH(Trauma) Trial observed reduced mortality with early surgery. 44 However, it is important to note that patients in this trial were mostly recruited in resource-limited settings where ICP monitoring was not usually available.…”
Section: Traumatic Intracerebral Hemorrhagementioning
confidence: 99%
“…temporal lobe or posterior fossa) often require surgical evacuation, especially if accompanied by radiological or clinical evidence of brainstem compression. The results of the STITCH (Trauma) trial are also expected to shed some light on the issue of surgical management of parenchymal mass lesions [8].…”
Section: Evacuation Of Intracranial Haematomasmentioning
confidence: 99%